2007
DOI: 10.1074/jbc.m609041200
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic Stress-dependent Repression Is Mediated by Histone H3 Phosphorylation and Chromatin Structure

Abstract: Histone H3 phosphorylation has been linked to various environmental stress responses and specific chromatin structure. The role of H3 phosphorylation in the osmotic stress response was investigated on the mouse mammary tumor virus (MMTV) promoter in different chromatin configurations. Hormone-dependent transcription from the MMTV promoter is repressed by osmotic stress when the promoter is integrated and has a normal chromatin structure. However, when the MMTV promoter is transiently transfected, the chromatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
7
1
Order By: Relevance
“…It has been shown that TLKs can phosphorylate histone H3 at the serine 10 position (Li Y, 2001). This histone modification has been shown to modulate transcription (Burkhart et al, 2007, Goto et al, 1999, Van Hooser et al, 1998, Lefebvre, 2002, Mahadevan et al, 1991). In latently infected cells, the KSHV ORF50 promoter is associated with repressive histone, which is released upon reactivation (Gunther and Grundhoff, 2010, Toth et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that TLKs can phosphorylate histone H3 at the serine 10 position (Li Y, 2001). This histone modification has been shown to modulate transcription (Burkhart et al, 2007, Goto et al, 1999, Van Hooser et al, 1998, Lefebvre, 2002, Mahadevan et al, 1991). In latently infected cells, the KSHV ORF50 promoter is associated with repressive histone, which is released upon reactivation (Gunther and Grundhoff, 2010, Toth et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, in both metazoans and plants, histone phosphorylation appears to be involved in responses to osmotic/salt stress (3,17,(19)(20)(21). In Arabidopsis the expression of most histone genes is down-regulated by dehydration conditions (43) and exposure of tobacco BY-2 cells to sucrose or NaCl resulted in induction of H3T3 phosphorylation (21).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of histone H3 is evolutionarily conserved at several sites including Ser 10 and 28 (H3S10ph and H3S28ph) and Thr 3 and 11 (H3T3ph and H3T11ph) (11)(12)(13)15). In metazoans, a variety of environmental stimuli can trigger histone H3 phosphorylation, both globally and at specific genes in interphase cells (11,14,(17)(18)(19). In plants, dynamic changes in histone H3 phosphorylation were also observed in cultured cells exposed to abiotic stress, such as high salt or low temperature, as well as to abscisic acid treatments (20,21).…”
mentioning
confidence: 99%
“…To ensure the quality of the anti-GR antibody ChIP’d DNA, we performed quantitative real time PCR (Q-RT-PCR) as previously described (13) on the promoter regions of SGK1 and TSC22D3/GILZ genes containing established GR binding regions (17, 18). The primers for SGK1’s promoter regions were: 5’-CCCCTCCCTTCGCTTGTT-3’ (sense) and 5’-GGAAGAAGTACAATCTGCATTTCACT-3’ (antisense) (19) ; the primers for TSC22D3/GILZ’s promoter regions were: 5’-GATACCAGTTAAGCTCCTGA-3’ (sense) and 5’-AGGTGGGAGACAATAATGAT-3’ (antisense) (20).…”
Section: Methodsmentioning
confidence: 99%